Implementation of the State Regulatory Policy in Ukraine - Malyga, Viktoriya (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article considers the peculiarities of the concept and implementation of the state regulatory policy in Ukraine. The content of the main features of such apolicy has been analyzed, its legal nature has been established and the most important problems of introduction of regulatory influence are revealed.
Keywords: regulacje prawne; Ukraina; polityka regulacyjna; sphere